The study of nickel effect on the hydrothermal dechlorination of PVC. (20th May 2017) - Zhao, Peitao; Li, Zhaozhi; Li, Tian; Yan, Weijie; Ge, Shifu
Abstract: The nickel might have involved in the hydrothermal (HT) treatment of poly(vinyl chloride) (PVC) containing wastes because of the corrosion of Ni-containing reactors, which was caused by the HCl generated in this process. This work has been conducted to investigate if the nickel has a positive effect on the HT dechlorination of PVC, which was usually neglected in previous research. The HT dechlorination of two kinds of PVC was performed in subcritical nickel-containing water with various Ni 2+ concentrations under several HT operating conditions in order to investigate the effect of the nickel on the dechlorination efficiency (DE). The FTIR, 13 C NMR and SEM techniques were utilized to characterize the hydrochars and the ICP-OES was used to measure the nickel content in the separated liquid (SL) to explore the possibility of reuse the nickel-containing water. The chlorine in the SLs was measured by potentiometric titration to solve the DE. The results show that the Ni 2+ could significantly accelerate the HT dechlorination of PVC at a relative mild condition. The DE was about 76% at a HT temperature of 220 °C for 30 min in 0.1 M Ni 2+ -containing water, 6 times higher than that without Ni 2+ . The HT temperature has a dominant effect on the DE which reached up to 87% at a HT temperature of 260 °C. At higher HT temperature, the acceleration of Ni 2+ was not obvious because of the aggravation of the corrosion and also the higher heat and mass transfer. Besides, the DE could not reach 100% at some circumstances because of the cyclization and cross-linking, which would be also weakened under higher temperature. According to the FTIR and 13 C NMR spectrum, both elimination and substitution happened during the HT dechlorination with Ni 2+ . The Ni 2+ could promote the evolution of the pores in PVCs and strengthen the substitution of Cl with OH, which was responsible for the acceleration of dechlorination at mild Ni 2+ -containing system. The ICP-OES result verified that the Ni 2+ worked as catalyst and the Ni 2+ -containing water could be reused. This result was beneficial for both the treatment of the nickel-containing wastewater and also the HT treatment of organic wastes. Graphical abstract: Highlights: Hydrothermal dechlorination of PVC was performed in subcritical nickel-containing water. Effects of Ni 2+ concentration on dechlorination efficiency was firstly investigated. The Ni 2+ could accelerate hydrothermal dechlorination of PVCs at mild conditions. FTIR and 13 C NMR were performed to reveal the mechanism. Dehydrochlorination was a main route for chlorine removal.